2013
DOI: 10.1093/qjmed/hct239
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism in patients treated for bacterial infection in the community with outpatient parenteral antimicrobial therapy

Abstract: This retrospective cohort study found a low incidence of VTE in OPAT patients, and does not support routine application of inpatient VTE prophylaxis algorithms to patients treated for infection in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Although key performance indicators for CRT during OPAT have not been agreed to, the frequency of CRT we observed during OPAT is comparable to that described in the published literature, which ranges from 0% to 6% of patients, 1,4 or 0.39–0.48 CRT per 1000 catheter days. 4,5 Whilst CRT were infrequent in our setting, their consequences were significant, with almost half (47%) resulting in unplanned readmission and 11% associated with pulmonary embolism.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Although key performance indicators for CRT during OPAT have not been agreed to, the frequency of CRT we observed during OPAT is comparable to that described in the published literature, which ranges from 0% to 6% of patients, 1,4 or 0.39–0.48 CRT per 1000 catheter days. 4,5 Whilst CRT were infrequent in our setting, their consequences were significant, with almost half (47%) resulting in unplanned readmission and 11% associated with pulmonary embolism.…”
Section: Discussionsupporting
confidence: 82%
“…A recent French study observed similar rates of readmission (75%) and pulmonary emboli (12%) amongst patients with CRT. 5 Treatment related adverse events and unplanned readmissions have been proposed as OPAT quality indicators, 8 and so risk of CRT has become a pressing issue for OPAT clinicians, 1 52% of whom report CRT amongst their patients within the last year. 8…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations